Gacha Addiction and In-App Purchases: A Study on Genshin Impact Players in Indonesia - Cokki Cokki; Haris Maupa; Wanstum Wanstum; Syarifuddin Sulaiman (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2025)
The purpose of this study was to examine the impact of gacha addiction and good price on the intention to purchase in-app items, with mobile game loyalty as a mediating variable. The research employed a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze survey data collected from 208 Genshin Impact players in Indonesia through random sampling and online questionnaires. The results indicate that gacha addiction significantly influences the intention to purchase in-app items, while good price has a moderate effect. Additionally, mobile game loyalty serves as a partial mediator in the relationship between gacha addiction and purchase intention. Keywords: Gacha Addiction; Genshin Impact; Good price; In-App Purchase Intention; Mobile game loyalty